2018
DOI: 10.1037/abn0000354
|View full text |Cite
|
Sign up to set email alerts
|

Rapid instruction-based task learning (RITL) in schizophrenia.

Abstract: Individuals with schizophrenia demonstrate broad impairments in neurocognitive functioning as measured through laboratory-based tasks. Neuropsychological measures depend on rapid instruction-based task learning (RITL), the ability to rapidly translate task instruction into goal-directed behavior. Here, the authors present the first known investigation of RITL in schizophrenia and aim to test whether RITL deficits exist in schizophrenia, are associated with abnormal brain activation, and contribute to the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…M. Silverstein et al 2012), early task-dependent processes have recently been shown to be impaired in schizophrenia. More specifically, rapid instructed task learning (RITL), the ability to rapidly transfer task instruction into goal-directed behavior, is reduced in schizophrenia, suggesting impaired learning processes (Sheffield et al 2018). Again, this overview is sparse compared to the impressive literature on cognitive impairment in chronic schizophrenia, but provides insight into the rich application of cognitive neuroscience research to understanding the generalized cognitive deficit across the life course of schizophrenia patients.…”
Section: Introductionmentioning
confidence: 99%
“…M. Silverstein et al 2012), early task-dependent processes have recently been shown to be impaired in schizophrenia. More specifically, rapid instructed task learning (RITL), the ability to rapidly transfer task instruction into goal-directed behavior, is reduced in schizophrenia, suggesting impaired learning processes (Sheffield et al 2018). Again, this overview is sparse compared to the impressive literature on cognitive impairment in chronic schizophrenia, but provides insight into the rich application of cognitive neuroscience research to understanding the generalized cognitive deficit across the life course of schizophrenia patients.…”
Section: Introductionmentioning
confidence: 99%
“…Tracking these fine-grained representational dynamics is crucial for a comprehensive understanding of the rapid neural re-organization processes that are taking place during early implementation trials right after first-time task instruction. Such rapid neural re-organization processes have been evidenced in terms of both mean activity dynamics (Cole et al, 2010; Hartstra et al, 2011; Ruge and Wolfensteller, 2010; Sheffield et al, 2018) and connectivity dynamics (Hampshire et al, 2019; Mohr et al, 2016; Mohr et al, 2018; Ruge and Wolfensteller, 2013). Specifically, conventional univariate analysis of mean activity has shown that lateral PFC engagement was maximal during the first-time implementation, followed by a rapid decline across the first few implementation trials (Hampshire et al, 2019; Hartstra et al, 2011; Ruge and Wolfensteller, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Tracking these fine-grained representational dynamics is crucial for a comprehensive understanding of the rapid neural re-organization processes that are taking place right after first-time task instruction. Such rapid neural re-organization processes have been evidenced in terms of both mean activity dynamics [16][17][18][19] and connectivity dynamics [20][21][22][23] . Specifically, conventional univariate analysis of mean activity has shown that lateral PFC engagement was maximal right after instruction, followed by a rapid decline across the first few implementation trials 16,17,23 .…”
Section: Introductionmentioning
confidence: 99%